TEACHERS’ PERCEPTION ON TEACHING ENGLISH TO STUDENTS WITH MILD MENTAL RETARDATION DURING THE COVID-19 PANDEMIC - wafiya ula (Language-Edu, 2022)
In Indonesia, the spread of positive cases of Covid-19 has not shown a decreasing graph. Due to the constraints on interaction, the Indonesian Ministry of Education issued a policy, which included closing schools and replacing the Teaching and Learning Activities process with an online system. Online learning is not limited to ordinary students but is also carried out on children with special needs or students with mild mental retardation, which in this case indicates that a person experiences a special disorder that has different characteristics so that special attention and services are needed. In an inclusive school, services for children with special needs are not differentiated from normal students in their class, only learning material is differentiated. The objective of this study is to describe how teaching-learning activities for children with minor mental retardation are implemented. during the covid-19 pandemic and to identify teachers’ perception on teaching English to students with mild mental retardation during the covid-19 pandemic of SMPN 6 Tuban. This study used qualitative research as its method. The English teachers from VIII C and IX B, as well as a special partner teacher from SMPN 6 Tuban, were the subjects of this study. The instruments of this research were observation, interview, and documentation.        The result of this research can be described that this is a new challenge for them because learning activity is done online. During the Covid-19 pandemic, teachers must still be able to provide curriculum and support pupils throughout the learning process. They use the media, method and also apply special principles for students with mild mental retardation. For special companion teachers, the limited face-to-face opportunity twice a week is an opportunity that must be utilized as well as possible because during online learning for students with mild mental retardation is too difficult to understand the material due to the absence of assistance and lack of attention from their parents. The teacher hopes that the students find happiness in learning through online learning classes they enjoy and can understand the material, especially for students with mild mental retardation. Based on the result of this research, the researcher found that in learning English, the activities that are more often used are the drilling method and copying simple words or vocabulary, so the materials and teaching methods used with students with mild mental retardation are different. The outcomes of teachers' perceptions of teaching English to students with mild mental retardation during the Covid-19 pandemic vary greatly, the section on teachers' perceptions reveals that teachers believe that learning English for students with mild mental retardation is difficult to do online because students with mild mental retardation face technological difficulties and obstacles. Because learning is done online, teachers find it more difficult to control the condition and development of students with mild mental retardation.Keywords: mental retardation students, perception